Menumbuhkan Kesadaran Pentingnya Pendidikan Anti-Korupsi di Era Maraknya Korupsi dalam Model Pembelajaran di SMPN 25 Pekanbaru - Nayla Fayza Salsabila; Tissa Oktavia Nurfadilla; Revalina Wulan Maharani; Delvia Aprianda; Shania Romadhona; Chindy Aulya Putri (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Corruption is an act that violates the law and aims to enrich oneself or others. Corruption can be carried out by individuals or organizations who have positions. Corruption can damage democratic values ​​and morality, as well as endanger economic and socio-political development. To prevent corruption, society can instill anti-corruption education from an early age, report corruption cases to the authorities, and monitor actions that could harm the state. This research was conducted as an educational material to raise awareness about anti-corruption starting from the school environment.